Development of android-based learning media assisted by Thunkable Applications in literary history courses - Fina Hiasa; Supadi Supadi; Emi Agustina; Meli Afrodita; Lazfihma Lazfihma; Nafri Yanti (BAHASTRA, 2023)
The purpose of this study was to develop learning media for Android-based Literary History using thunkable applications in the independent learning-free campus era. This study applied the Research and Development method whose products were tested on students. Therefore media validation and material validation are needed before it is finally validated by the user. Research data collection uses a questionnaire so that it is known about the feasibility of the product in the form of thunkable application-assisted learning media. This study concluded that the total score of the combined validation questionnaire was 129 or 4.03 as the average. In other words, these results state the feasibility of android-based modern Indonesian literature learning media assisted by the thunkable application for use in teaching and learning activities in Literary History courses.